Becoming a deliberately developmental organization: Using competency based assessment data for organizational development. (3rd July 2021) - Thoma, Brent; Caretta-Weyer, Holly; Schumacher, Daniel J.; Warm, Eric; Hall, Andrew K.; Hamstra, Stanley J.; Cavalcanti, Rodrigo; Chan, Teresa M.; ,
Abstract: Medical education is situated within health care and educational organizations that frequently lag in their use of data to learn, develop, and improve performance. How might we leverage competency-based medical education (CBME) assessment data at the individual, program, and system levels, with the goal of redefining CBME from an initiative that supports the development of physicians to one that also fosters the development of the faculty, administrators, and programs within our organizations? In this paper we review the Deliberately Developmental Organization (DDO) framework proposed by Robert Kegan and Lisa Lahey, a theoretical framework that explains how organizations can foster the development of their people. We then describe the DDO's conceptual alignment with CBME and outline how CBME assessment data could be used to spur the transformation of health care and educational organizations into digitally integrated DDOs. A DDO-oriented use of CBME assessment data will require intentional investment into both the digitalization of assessment data and the development of the people within our organizations. By reframing CBME in this light, we hope that educational and health care leaders will see their investments in CBME as an opportunity to spur the evolution of a developmental culture.